World Bank Research Digest, Vol. 13(3) - World Bank (World Bank, Washington, DC, 2019)
This issue focuses on Urbanization and Infrastructure Development and features the following articles:Building Sustainable Cities and Efficient Infrastructure; Who Benefits from Investments in Bus Rapid Transit Systems? Evidence from Colombia; Beyond Faster Travel: Assessing the WiderEconomic Benefits of Transport Corridors; A Big Push or a Backwash? Economic Effects of Connecting a Hinterland; Highway Politics in Mexico; How Does the Shape of Latin American Cities AffectTheir Productivity? Getting to Jobs in Nairobi; Public Infrastructure and Structural Transformation; Buses, Houses, or Cash? Choices and Consequences in Reforming Public Transport Subsidies; Improving the Resilience of Peru’s Road Network to Climate Events; and The Vulnerability of Manufacturing Firms to Unreliable Water Infrastructure.